Analysis of Hedonic Shopping Value, Fashion Involvement on Impulse Buying with Shopping Lifestyle and Positive Emotion as Intervening Variables in Malls: Analisis Hedonic Shopping Value, Fashion Involvement terhadap Impulse Buying dengan Shopping Lifestyle dan Positive Emotion sebagai Variabel Intervening pada Mall - Yuhanda, Rihadatul Aisy; Indayani, Lilik; Rizal, As’at; Sari, Dewi Komala (Indonesian Journal of Innovation Studies, 2021)
This study aims to determine the Hedonic Shopping Value Analysis, Fashion Involvement of Impulse Buying with Shopping Lifestyle and Positive Emotion as Intervening Variables at SOGO Tunjungan Plaza Surabaya. The sample used is 100 respondents. Samples were taken by incidental sampling method. The data analysis technique used is PLS-SEM analysis with the SmartPLS 3.0 program. The results of this study indicate that Hedonic shopping value has an effect on impulse buying. Fashion involvement has an effect on impulse buying. Hedonic shopping value has an effect on shopping lifestyle. Shopping lifestyle has an effect on fashion involvement. Hedonic shopping value has an effect on positive emotion. Fashion involvement has an effect on positive emotion. Hedonic Shopping Value has an effect on impulse buying. Shopping lifestyle has an effect on positive emotion. Positive emotion has an effect on impulse buying.